Linguistics Vanguard : A Multimodal Journal for the Language Sciences (De Gruyter Mouton, 2015)
Linguistics Vanguard is a new channel for high-quality articles in all major fields of linguistics. Published solely online, the multimodal journal provides an accessible platform supporting both traditional contributions as well as innovative publications featuring interactive content. Linguistics Vanguard publishes concise and up-to-date reports on the state of the art in linguistics as well as cutting-edge research papers.